Усереднення квазілінійної параболічної задачі з різними нелінійними крайовими умовами Фур'є, що чергуються, в дворівневому густому з'єднанні типу 3:2:2 - Мельник, Т.А.; Садовий, Д.Ю. (Український математичний журнал, 2011)
Исследуется асимптотическое поведение решения квазилинейной параболической краевой задачи в густом двухуровневом соединении типа 3 : 2 : 2. Такое соединение состоит из цилиндра, на который ε-периодически нанизаны тонкие диски с переменной толщиной. Тонкие диски разделены на два уровня в зависимости от их геометрической структуры, а также от краевых условий, заданных на их границах. В данной задаче рассматриваются различные неоднородные нелинейные условия Фурье, которые чередуются. Кроме того, условия Фурье зависят от дополнительных параметров возмущения. В зависимости от этих параметров доказаны теоремы сходимости для решения такой задачи при ε→0. We investigate the asymptotic behavior of a solution of a quasilinear parabolic boundary-value problem in a two-level thick junction of the type 3:2:2. This junction consists of a cylinder on which thin disks of variable thickness are ε-periodically threaded. The thin disks are divided into two levels, depending on their geometric structure and the conditions imposed on their boundaries. In this problem, we consider different alternating inhomogeneous nonlinear Fourier conditions. Moreover, the Fourier conditions depend on additional perturbation parameters. We prove theorems on the convergence of a solution of this problem as ε→0 for different values of these parameters